Efektivitas Pendekatan Culturally Responsive Teaching (CRT) Dalam Meningkatkan Hasil Belajar Siswa Pada Materi Kekayaan Budaya Indonesia Di Kelas IV SD Negeri 060910 Medan Denai - Sihaloho, Tiodora Anggie; Bahri, Samsul; Ginting, Lisa Septia Dewi Br; Sriwahyuni, Titi Lestia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to assess how well the Culturally Responsive Teaching (CRT) method has helped fourth grade students at SD Negeri 060910 Medan Denai understand about Indonesian Cultural Wealth. Twenty-five students participated in a Classroom Action Research (CAR) project consisting of two parts. In order to make the information more relevant and contextual for the students, the CRT approach incorporated local cultural components into the learning process. The completion rate of the study participants increased from 64% in the first cycle to 89% in the second cycle. Not only did the students' cognitive abilities improve, but their engagement and appreciation for cultural diversity also increased. The CRT method has succeeded in developing the students' personalities in a way that respects their culture and national identity while also fostering a friendly and stimulating environment for all students.